The Meaning Behind Financial Governance Accountability Indigenous Communities - Suwitra, Wayan Arik; Bayu Putra, Cokorda Gde; Putri Agustina, Made Dian (Management and Applied Social Studies Review, 2023)
Purpose – This study aims to answer the Because of Motives and In Order to Motives Agent of accountability events in Nyingkrem practices in Customary Sub-Village of Gelulung, Sukawati Customary Village. Methodology – Qualitative methods with a phenomenological approach were applied in this study. Data collection is conducted through interviews, observation and documentation. The informant of this research was taken from the administrator of banjar Adat (customary sub-village) Gelulung Findings – The results of the study revealed that the motives of the Agent of events in interpreting accountability were based on the motive to maintain Balinese tradition (dresta), in an effort to respect the services of ancestors. The sacred procession of deification of witnesses and cane offerings is a form of spirituality accountability. And the banjar administrator accountability to society at large implicitly presents horizontal accountability.